Analisis Sisa Makanan Pasien Rawat Inap Rumah Sakit - Sumardilah, Dewi Sri (Poltekkes Kemenkes Tanjung Karang, 2022)
Kepmenkes No.129/Menkes/SK/II/2008 concerning Minimum Hospital Service Standards (SPM) states that as much as 20% of food leftovers are not eaten by patients. Patient nutrition becomes inadequate and inefficient due to wasted costs. This study aims to analyze food waste from inpatients at the hospital. Using a cross-sectional design, measurements were made of 113 inpatients at Ahmad Yani Metro Hospital, taken proportionally from classes I, II, and III with the consecutive method. As the dependent variable is leftover food and the independent variable is food appearance (portion and serving), food taste (seasoning and food temperature), and food from outside the hospital. Data were collected by interview technique using a closed list of questions and assessment using the Comstock Form. The analysis will be carried out to the bivariate level using a t-test. The results of this study indicate that 79.6% of inpatients at the Ahmad Yani Hospital in Metro City left less than 20% of food left. Meanwhile, the average leftover food reached 18.5% (SD=14.7%). There was a relationship between food presentation (p-value=0.018), food temperature (p-value=0.048), and food from outside the hospital (p-value= 0.044) with leftover food. Meanwhile, the portion of food (p-value=0.178) and seasoning (p-value=0.115) had no significant relationship with food waste. Therefore, it is recommended to hospitals as nutrition service providers improve the vegetable menu in the menu cycle.